Control de factores medio ambientales en el comportamiento reproductivo de cuyes en el CEASA. - Guacho Alvarez, Juan Francisco (2023)
The research was conducted at the Salache Academic Experimental Center, of the Technical University of Cotopaxi. The objective was to evaluate environmental factors on reproductive behavior in the guinea pig breeding system. Using a quantitative methodology since data was collected by observing the different parameters in our project, that they were then synthesized for a better interpretation; using statistical analysis, with three treatments at different densities 8*0.05m2, 7*0.05m2 and 6*0.05m2. The consumption of food, water, weights of the mother, father and calf was analyzed, as well as the mortality in each of the treatments obtaining the following results; T1 starts with a consumption of 12,655, T2 12,038 ending with 13,016 and T3 12,032 at 4 weeks 12,701 analyzing that there is no major difference in consumption. In relation to treatment 1, water consumption per week is 862.3 ml., and the third place is treatment 3 with a water consumption of 866.55 ml. In reference to the weight of the mother and father on the offspring there is a significant difference with the weight of the father while there is no significant difference with the mother's weights. In mortality, treatment 3 expresses the highest percentage of mortality with 13.3%, treatment 2 with 6.6% and treatment 1 with 2.2%, concluding that there is no major difference in the weights of the mother and father since they are in similar weights. Recommending permanent evaluations on the principle of housing to avoid a critical number of mortalities.